The Effect of Tank Background Colour and Stocking Density On The Growth and Survival Rate of Siammese Catfish Larvae (Pangasius hypophthalmus) - Puja Andini; Hamdan Alawi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study was carried out to evaluate the combined effects of four background tank color and two stocking density on growth and survival rate of stripped catfish Pangasius hyophthalmus larvae reared with a water recirculation system.The fish larvae (0,002 g) were reared in aquarium with white, black, Blueand clear backgoround at two stocking densities of 5 fish/L (75 fish/aquarium)and 10 fish/L ( 150 fish/aquarium). The inside walls and the bottom of each aqauarium were laminated with colored water resistant paper to achieve the background color tested (white, black and blue) while nonlaminated (clear) aquarium serves as a control. The larvae were fed on tubifex worms trice a day for 40 days rearing period. The best growth- weight, length and specifc growth rate were obtained for larvae reared at 5 fish /L stocking densities. While Survival rate of larvae was not significantly diferent with 96,3% for larvae stocked at 5/L and 95,75% for larvae stocke at 10/L respectively. The darker background color aquarium (black and blue) significantly gave better growth rates compared to those clearer ones (white and clear aquarium). The result seggested that Pangasius hypophthalmus larvae shiud be reared at 10 fish/L aquarium with black background. Keywords : Background colour, Stocking denstity,Siammese Catfish Larvae,